CULTURALLY RESPONSIVE LANGUAGE PEDAGOGY: INTEGRATING INDIGENOUS LANGUAGES INTO MODERN EDUCATIONAL FRAMEWORKS - Tomas Garcia (Modern American Journals, 2025)
Culturally responsive pedagogy (CRP) has emerged as a crucial approach for fostering educational equity and inclusion, particularly for marginalized communities. This research explores the integration of Indigenous languages within contemporary educational frameworks through a culturally responsive lens. By examining case studies of successful language revitalization programs and pedagogical practices from various Indigenous communities, this paper demonstrates the transformative power of Indigenous language education in promoting not only linguistic diversity but also cultural identity, social cohesion, and community empowerment. The study further investigates the role of educators, curriculum developers, and policymakers in supporting the inclusion of Indigenous languages in the classroom. We conclude by presenting actionable recommendations for integrating Indigenous languages into mainstream education systems, emphasizing the importance of respect for cultural heritage, student-centered teaching practices, and community involvement in curriculum design.
Keywords: Culturally Responsive Pedagogy, Indigenous Languages, Language Revitalization, Educational Frameworks, Linguistic Diversity, Curriculum Development, Educational Equity, Language Teaching Practices